Performance Evaluation and Microstructural Assessment of Industrial Solid Waste as Sustainable Additives for Expansive Soil - Muhammad Nadeem; Sami Ullah; Mohammad Arsalan Khan; Shanxiong Chen; Meshel Q. Alkahtani; Mohammad Mursaleen; Rania Salih; Dildar Ali; Li Jian; Jamal Ahmad; Saiful Islam (Advances in Civil Engineering)
Expansive soils pose significant challenges in civil engineering due to their susceptibility to volumetric changes, leading to structural instability and damage in infrastructure. This study evaluates the performance and microstructural characteristics of industrial solid waste materials (Class F-fly ash and ground granulated blast-furnace slag) as additives for stabilizing expansive soils. Tests, including moisture density, unconfined compressive strength, Atterberg limits, compressibility index (Cc), cation exchange capacity, direct shear test, and California bearing ratio, were conducted on the treated expansive soil. Scanning electron microscopy and energy dispersive X-ray spectroscopy (EDX) were used to analyze the changes in the soil matrix due to the incorporation of the waste materials. The results demonstrate improved engineering properties of expansive soil treated with these additives. The analysis confirms enhancements in particle arrangement, reduced porosity/pore sizes, and improved bonding between soil particles, indicating the formation of calcium silicate hydrate and calcium aluminate hydrate. This research suggests that these waste materials can be eco-friendly and cost-effective alternatives for stabilizing expansive soils in construction projects.